First Nations Child Removal and New South Wales Out-of-Home Care: A Historical Analysis of the Motivating Philosophies, Imposed Policies, and Underutilised Recommendations - James C. Beaufils (Genealogy)
Interactions between First Nations and non-Indigenous Australians have long been shaped by notions of Western authority and First Nations inferiority, both culturally and biologically. From invasion to the present day, forced removals and intergenerational trauma have deeply affected First Nations Australians, particularly through the operations of interacting colonial systems, including child removals and placements. Throughout the 20th century, systematic child removals led to the Stolen Generations, a tragic example of power imbalances, paternalism, and Western ideals, perpetuating trauma across generations. This article examines the context of First Nations removals by the state under the lies of benevolence, exposing the evolution of the colonial system and the systematic dislocation of culture and identity. It highlights the social, legal, and political factors that enabled removal practices and their enduring consequences, including the legacy of forced child separations and cultural erasure. This article argues that policies of absorption and assimilation served to further isolate children from their families, communities, and kinship networks. In doing so, it contends that the systematic disruption of First Nations communities is part of an ongoing process of subjugation, continuing the colonial agenda of cultural and familial disintegration.